Energy absorption capability of thin-walled aluminium tubes under crash loading - Khalili P.; Tarlochan F.; Hamouda A.M.S.; Al-Khalifa K. (Universiti Malaysia Pahang, 2023)
This paper investigates the interaction of design factors such as tube thickness, tube length, and tube cross-sectional aspect ratio, along with friction and impacting mass on crashworthiness parameters such as specific energy absorption contact time, peak force and crush distance. The impact velocity is assumed to be constant at 15 m/s. The focus is on rectangular aluminium tubes and the analysis was carried out by using a validated finite element model. The analysis shows that the factors are not independent of each other and there is some degree of interaction between them. It was found that the trigger mechanism is a very important design factor to be included in the design of thin-walled tubes for energy absorption applications. The effect of the friction coefficient was found to be insignificant and finally, based on the interactions, it can be concluded that the most effective design would be a larger tube with small wall thickness, and a larger aspect ratio to avoid buckling. 2015 Universiti Malaysia Pahang, Malaysia.